Revista Vida: o habitus católico e o tempo do homem - Oliveira, Pablo Matheus Andrade Trajano de (2019)
This dissertation analyzes and discusses questions related to the presence and performance of young university leaders linked to the Catholic Church, institution of the religious field, in cultural and political activities of Brazilian civil society, in the years 30/40 of the twentieth century. In this perspective, we analyze the Brazilian aspects of the so-called Schools of Fear (Fascism, Integralism) and its opposite, the School of Dialogue (integral humanism), relating them to the social changes that the Catholic Church faced in this period and how this influenced the Brazilian religious field. The work is dedicated to the 38 issues of this publication of university students of the Catholic University Action (AUC), linked to the Dom Vital Center in Rio de Janeiro, which was published between April 1934 and October 1937, when it was interrupted by the decree of the State New. During these years the magazine reflected the positioning and the questionings of a group of young Catholic intellectuals in face of the great social and religious changes of the time. The study of Magazine VIDA allows us to take as a counterpoint the thought of a group that, in successive decades, would mark progressive Catholic thinking in Brazil. As well as, the participation of the intellectuals in the national life was supported in the belief that they were an elite able to ―save‖ the country. The proposal of Magazine VIDA, as a means of communication, was to become a meeting point of the daring thoughts of university students to a time in which the intellectuals brought to themselves the responsibility to command several instances of the National State. We select a set of articles in which the contrast between the tributary discourses of the schools of "fear" and "of the dialogue", the search for ecclesial participation and political protagonism, will be better understood. On these, then, we have made an analysis with the instruments of Social History. We use Pierre Bourdieu's field concepts and habitus as theoretical reference, both of which are concepts that attempt to explain the mechanisms of socialization and action of the individual in society, identifying patterns of behavior and social reproduction. In order to achieve the objectives, the paths of bibliographic-documentary research and of documentary research were traced.